2006
DOI: 10.1007/s00415-006-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Alzheimer’s disease from subcortical vascular dementia with the FAB test

Abstract: The FAB test can provide useful information for differentiating AD and VD at the bedside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 20 publications
3
46
0
1
Order By: Relevance
“…Existing validation studies observed cutoffs of 11/12 for executive dysfunction in subcortical infarct (Sn: 69.2%, Sp: 87.7%, Ac: 80.6%) [9] and differentiated AD (cutoff 11/12; Sn: 77%, Sp: 87%) [2] from frontotemporal dementia (cutoff 10/11; Sn: 85–92%, Sp: 85%) [8]. The cutoff scores in our study are more similar to the normative values in an Italian population control sample [15]. This is likely related to the fact that we included subjects in the earlier stages of cognitive impairment with CDR scores ≤1 [37] and the use of community-dwelling healthy elderly controls who met the operational definition of cognitively normal (in contrast to including subjects presenting to the specialist memory clinic with subjective memory complaints who were subsequently diagnosed as normal following evaluation).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Existing validation studies observed cutoffs of 11/12 for executive dysfunction in subcortical infarct (Sn: 69.2%, Sp: 87.7%, Ac: 80.6%) [9] and differentiated AD (cutoff 11/12; Sn: 77%, Sp: 87%) [2] from frontotemporal dementia (cutoff 10/11; Sn: 85–92%, Sp: 85%) [8]. The cutoff scores in our study are more similar to the normative values in an Italian population control sample [15]. This is likely related to the fact that we included subjects in the earlier stages of cognitive impairment with CDR scores ≤1 [37] and the use of community-dwelling healthy elderly controls who met the operational definition of cognitively normal (in contrast to including subjects presenting to the specialist memory clinic with subjective memory complaints who were subsequently diagnosed as normal following evaluation).…”
Section: Discussionsupporting
confidence: 60%
“…Most of the previous work on the FAB has focused on the differentiation of Alzheimer’s disease (AD) from frontotemporal dementia [11,12,13,14], subcortical vascular dementia (VaD) [15] and (more recently) dementia with Lewy Body [16]. Existing validation studies report a range of cutoffs, either in the use of the FAB for detecting executive dysfunction in subcortical infarct (cutoff 11/12 [9]) or for differentiating AD from frontotemporal dementia (cutoff 11/12 [11] and 10/11 [14,17]).…”
Section: Introductionmentioning
confidence: 99%
“…The Frontal Assessment Battery (FAB; Dubois, Slachevsky, Litvan, & Pillon, 2000 ) is an executive screening test that, over the last years, has become widely used in neurological research (Guedj et al, 2008 ;Lima, Meireles, Fonseca, Castro, & Garrett, 2008 ;Oguro et al, 2006 ;Santangelo et al, 2009 ;Yoshida et al, 2009 ). It consists of six subtests assessing conceptualization, cognitive fl exibility, motor programming, sensitivity to interference, motor inhibitory control, and prehension behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have examined the discriminative ability of the FAB for patients with AD and vascular cognitive impairment (VCI) [24,46,47]. Taking into consideration performance on individual subtests in addition to the total score of the FAB has generally been reported to result in better discriminative power [24,46].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have discovered that neural substrates related to performances on the FAB include both cortical and subcortical areas, such as the middle frontal gyrus, inferior frontal, insula [22], callosomarginal, and precentral regions [23]. Previous studies have also shown that the FAB is useful in differentiating AD from subcortical VaD [24]. However, the discriminative power of the FAB at an earlier pre-dementia stage and the neural correlates of FAB performance have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%